2007
DOI: 10.1007/s12088-007-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of mutants of Pseudomonas maltophila PM-4 altered in chitinolytic activity and antagonistic activity against root rot pathogens of clusterbean (Cyamopsis tetragonoloba)

Abstract: Pseudomonas maltophila PM-4, an antagonist of pathogenic fungi including Rhizoctonia bataticola, R. solani, Fusarium oxysporum and Sclerotinia sclerotiorum associated with root rot of clusterbean (Cyamopsis tetragonoloba) was mutagenized with Tn5. Hyperchitinase producing mutants showing large zone of colloidal chitin dissolution were identifi ed on medium containing calcofl or dye as an indicator. A mutant P-48 producing 137% higher chitinase activity than the parent strain PM-4 was identifi ed. Seed bacteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…It is also clear that application of VAM and B. megatherium increased both the amounts of the available nutrients in soil, plant growth, soil fertility and counts of microbial communities. These results agree with those obtained by Yadav et al (2007) and Daneshmandi et al (2012). …”
Section: Microbial Activities In Rhizospheresupporting
confidence: 94%
“…It is also clear that application of VAM and B. megatherium increased both the amounts of the available nutrients in soil, plant growth, soil fertility and counts of microbial communities. These results agree with those obtained by Yadav et al (2007) and Daneshmandi et al (2012). …”
Section: Microbial Activities In Rhizospheresupporting
confidence: 94%
“…The highest increase in Bacillus counts were obtained by using the T11, followed by T10 and T6 application. The promoting effect due to the production of plant growth promoting substances as well, which increase soil fertility, microbial communities and plant growth (Yadav et al, 2007). These results are in agreement with those obtained by Ashrafuzzaman et.…”
Section: Bacillus Countssupporting
confidence: 92%
“…The basis of the beneficial effect of compost tea on fruit set and decreased fruit drop is due to that compost tea has an improvement effect on the nutritional status of the plant as a result of its content (macro and micronutrients and in addition to the high value of useful bacteria, fungi and actinomycetes) in the solution. These results are in line with Yadav et al (2007), who found that the organic fertilizers and bio fertilizers are enhancing the initial fruit setting of mango. Moustafa (2002) found that compost tea was the most efficient in enhancing tree fruiting of Washington navel orange trees, hence it increased fruit set percentage, reduced fruit drop.…”
Section: Fruit Set and Fruit Dropsupporting
confidence: 91%
“…The highest increase in Pseudomonas densities were obtained by using the interaction treatment with magnetic iron application treatments (0, 50, 100 and 150 kg/fed, respectively). The promoting effect due to the application of P. flouresence not only to the production of organic acid and siderophore which increased the availability of iron uptake but also to the production of plant growth promoting substances and antimicrobial substances as well which increase soil fertility, microbial communities and plant growth (Yadav et al, 2007). Anandaraj & Leema (2010) confirmed that, combined inoculation increased the population of total bacteria, Rhizobium sp.…”
Section: Pseudomonas Densitiesmentioning
confidence: 94%